KARAKTERISTIK BRIKET AMPAS TEBU DAN TONGKOL JAGUNG DENGAN PEREKAT TEPUNG SAGU - Afandi, Riyan; Hamzah, Farida Hanum; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to determine the characteristics of charcoal briquette from a mixture of bagasse and corncob quality according to 01-6235-2000. Research using a Completely Randomized Design (CRD) with comparison bagasse and corncob (P1= 100:0%); (P2= 75:25%); (P3= 50:50%); (P4= 25:75%); (P5= 0:100%). The result showed that variations in mix charcoal bagasse and corncob significantly affected moisture content, ash content, calorific value, volatile matter, and fixed carbon content briquettes. The result showed that the best treatment in treatment P2 namely briquettes are made with 75% charcoal bagasse and 25% charcoal corncob with levels of moisture content 6.8979%, ash content 5.3043%, calorific value 5177 cal.g-1, volatile matter 14.8326 %, and fixed carbon content 73.5828%.Keywords: Charcoal briquettes, bagasse, corncob